Comparison of Lysis Buffers for Saliva DNA Extraction using Modified Magnetic-Silica Nanoparticle Beads - Muhammad Fauzi Arif; Ahadi Damar Prasetya; Indra Lesmana; Niken Satuti Nur Handayani (Biotropika: Journal of Tropical Biology, 2023)
Our previous study revealed that modified MAGSi (magnetic-silica nanopartivel beads) had various sizes and shapes that affected the DNA extraction process. In this study, we combined our MAGSi with several kinds of lysis buffer for DNA extraction to analyze the result. Human saliva DNA was extracted using three kinds of MAGSi. Each of them was made differently. We used ATL buffer, Triton Buffer, and without buffer for cell lysis. The concentration and purity of the extracted DNA were analyzed using spectrophotometry. Extracted DNA also was used as template DNA for DNA amplification using beta globin gene. This study revealed that our MAGSi-1 provided the best result for DNA concentration and purity. This study also revealed that DNA extraction using lysis buffer produced less concentration yield and purity value but it was more consistent. The concentration and purity value were different but consistent. All the extraction can be used as DNA template for amplification of human beta globin gene. Further studies are still needed to determine the effectiveness and consistency of the lysis buffer and our MAGSi.